MICHAEL W. MEHAFFY - Cities Alive. Jane Jacobs, Christopher Alexander, and the Roots of Urban Renaissance - Monclús Fraga, Javier (ZARCH, 2023)
Michael W. MehaffyCities Alive. Jane Jacobs, Christopher Alexander, and the Roots of Urban RenaissancePortland, Oregon (USA): Sutasis Press, 2017. 288 pp. Tapa blanda. Idioma: inglés. 19 €ISBN: 978-9463864046